Verbum e ius Predicazione e sistemi giuridici nell'Occidente medievale / Preaching and legal Frameworks in the Middle Ages - Parrinello, Rosa Maria; Gaffuri, Laura (Reti Medievali E-Book, 2018)
The theme of the relationship between Verbum and ius, between faith, natural law and positive law, was the core of an intense debate during the Middle Ages. It was not restricted to the centres of knowledge; on the contrary, the ecclesiastical entrusted it to pastoral practices with the aim of having a concrete influence on the drafting of religious, civilian and state laws and regulations. The essays collected in this volume focus on that debate, investigating mainly the preaching and preachers who turned the erudite speeches by exegetes, theologians, jurists and magistri on the concepts of law, community and faith into "public communication".